2009
DOI: 10.1523/jneurosci.3923-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Inhibitory Dysfunction Induces a Selectively Dynamic, Morphine-Resistant, and Neurokinin 1 Receptor- Independent Mechanical Allodynia

Abstract: Dynamic mechanical allodynia is a widespread and intractable symptom of neuropathic pain for which there is a lack of effective therapy. We recently provided a novel perspective on the mechanisms of this symptom by showing that a simple switch in trigeminal glycine synaptic inhibition can turn touch into pain by unmasking innocuous input to superficial dorsal horn nociceptive specific neurons through a local excitatory, NMDA-dependent neural circuit involving neurons expressing the gamma isoform of protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
118
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 70 publications
10
118
0
Order By: Relevance
“…In one scenario, warm-sensitive neurons affected by hindpaw burn would become hyperexcitable due to changes in the electrophysiological properties of Na v 1.7 and would produce more action potentials in response to their adequate stimulus (e.g., 40°C). It is not entirely clear in this case how warm-sensitive afferents would gain the ability to communicate via heat-pain pathways in the spinal cord, although a system analogous to the disinhibition demonstrated in touch-pain for the mechanical modality (Yaksh, 1989;Sivilotti and Woolf, 1994;Torsney and MacDermott, 2006;Miraucourt et al, 2009) could be involved. This would require warm-sensitive neurons to be prewired to second-order pain-sensitive neurons, and additionally invokes changes in spinal interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…In one scenario, warm-sensitive neurons affected by hindpaw burn would become hyperexcitable due to changes in the electrophysiological properties of Na v 1.7 and would produce more action potentials in response to their adequate stimulus (e.g., 40°C). It is not entirely clear in this case how warm-sensitive afferents would gain the ability to communicate via heat-pain pathways in the spinal cord, although a system analogous to the disinhibition demonstrated in touch-pain for the mechanical modality (Yaksh, 1989;Sivilotti and Woolf, 1994;Torsney and MacDermott, 2006;Miraucourt et al, 2009) could be involved. This would require warm-sensitive neurons to be prewired to second-order pain-sensitive neurons, and additionally invokes changes in spinal interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory interneurons of the spinal dorsal horn have been proposed to gate the flow of innocuous and nociceptive sensory information from the periphery to higher brain centers (12), and supportive evidence for this idea is growing (13)(14)(15)(16)(17). Loss of GABAergic/glycinergic inhibition contributes to enhanced transmission of nociceptive signals through the dorsal horn circuit during pain states, resulting in hyperalgesia and allodynia (3,(18)(19)(20). For example, polysynaptic A-fiber inputs onto neurokinin 1 receptor (NK1R)-expressing projection neurons become apparent only when GABA A R and GlyRs are pharmacologically blocked, indicating that under conditions of disinhibition, nonnoxious mechanical stimuli can drive nociceptive-specific projection pathways and elicit allodynia (21).…”
mentioning
confidence: 99%
“…The similarities of intracisternal strychnine-induced glycine disinhibition to clinical trigeminal neuropathy include the presence of dynamic allodynia 1 and its restriction to the distribution of the trigeminal nerve distribution. 4 Strychnine did not produce changes in sensorimotor activity in areas other than the trigeminal distribution, allowing for assessment of nervous system dysfunction specific to the trigeminal nerve.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, trigeminal glycinergic inhibitory dysfunction has been shown in rats to produce localized dynamic allodynia, a central feature of human trigeminal neuralgia. 4,5 While electrophysiological, behavioural, and pharmacological studies in vivo have shown that this produces many of the features of clinical trigeminal neuropathies, the model requires validation for clinically effective agents. 6 Nonetheless, the clinically ineffective agent, morphine, has also been shown to be ineffective in reversing rat dynamic mechanical allodynia resulting from strychnine-induced allodynia.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation